A review of the evidence for endocrine disrupting effects of current-use chemicals on wildlife populations. (16th March 2018) - Matthiessen, Peter; Wheeler, James R.; Weltje, Lennart
Abstract: This review critically examines the data on claimed endocrine-mediated adverse effects of chemicals on wildlife populations. It focuses on the effects of current-use chemicals, and compares their apparent scale and severity with those of legacy chemicals which have been withdrawn from sale or use, although they may still be present in the environment. The review concludes that the effects on wildlife of many legacy chemicals with endocrine activity are generally greater than those caused by current-use chemicals, with the exception of ethinylestradiol and other estrogens found in sewage effluents, which are causing widespread effects on fish populations. It is considered that current chemical testing regimes and risk assessment procedures, at least those to which pesticides and biocides are subjected, are in part responsible for this improvement. This is noteworthy as most ecotoxicological testing for regulatory purposes is currently focused on characterizing apical adverse effect endpoints rather than identifying the mechanism(s) responsible for any observed effects. Furthermore, a suite of internationally standardized ecotoxicity tests sensitive for potential endocrine-mediated effects is now in place, or under development, which should ensure further characterization of substances with these properties so that they can be adequately regulated.